The Effect of Profitability, Financial Leverage, and Winner/Loser Stock to Income Smoothing - Dihanti Yusman, Nur; Asmeri, Rina; Gusraini, Neti; Novri Andra, Ikhvan (Dinasti Publisher, 2021)
This study aims to find out: (1) the effect of profitability on the occurrence of income smoothing practices, (2) the effect of financial leverage on the occurrence of income smoothing practices, (3) the effect of winner/loser stock on the occurrence of income smoothing practices, and (4) the effect of profitability , financial leverage, winner/loser stock on the occurrence of income smoothing practices simultaneously. This research was conducted using Statistical Analysis method. The statistical analysis method used here is logistic regression analysis. Where in the statistical regression analysis test will be tested in it: (1) testing the feasibility of the regression model, (2) assessing the entire model, (3) Coefficient of Determination, (4) Multicollinearity Testing, (5) Classification Matrix, and (6) Model Formed Regression. The results obtained from this study: (1) profitability has no effect on the occurrence of income smoothing practices, (2) financial leverage does not affect the occurrence of income smoothing practices, (3) winner/loser stock does not affect the occurrence of income smoothing practices, and (4 ) profitability, financial leverage, winner/loser stock have no effect on the occurrence of income smoothing practices simultaneously.